Sharpe's storm [large type] : Richard Sharpe and invasion of southern France,1813 - Cornwell, Bernard (Cornwell, Bernard. Richard Sharpe series., 2025)
"The year is 1813. France is a battlefield, and winter shows no mercy. Amid brutal conditions, Major Richard Sharpe finds himself saddled with an unexpected burden: Rear-Admiral Sir Joel Chase, dispatched by the Admiralty with sealed orders, unshakable confidence, and a frankly terrifying enthusiasm for combat. Sharpe's mission from Wellington is clear, yet anything but simple: keep Sir Joel alive. SirJoel could hold the key to defeating Napoleon once and for all. Butto pull off his audacious plan, he needs someone who knows how to fight dirty, think fast, and survive the impossible"--